Students’ Intention (as a Consumer) to Study through Distance Education Mode Post COVID-19 Crises - Kashyap, Heena; Makhija, Sunny (Indian Journal of Educational Technology, 2021)
The aim of this paper is to assess the intention of students (as a consumer) to study through distance education mode after arousal of a pandemic situation (due to spread of coronavirus all over the world). The research was conducted in India, where responses were sought from current and prospective students. The basic idea was to study the impact of covid-19 crises on the mindset of students, as many of them would be hesitant in travelling miles for a regular college. While searching for the best college/education institution, the behavior of students seems to be similar to the behavior of a consumer. Therefore, students’ intention was studied from the perspective of consumer behavior discipline. There were a total 431 students whose responses were included in this study. The smart PLS version 2.0 software has been used for applying mathematical and statistical formulas. The model was constructed from the literature review that consisted of four independent factors (perception, attitude, motivation and personality) and one dependent factor (student/consumer intention). The results showed that perception, attitude and motivation are the main driving force behind a student’s intention to take admission in a distance education institution.